P.144 Patient-relevant deficit dictates EVT decision-making in low NIHSS patients with medium vessel occlusion stroke. (November 2021) - McDonough, RV; Cimflova, P; Kashani, N; Ospel, JM; Kappelhof, M; Singh, N; Segal, A; Sakai, N; Fiehler, J; Chen, M; Goyal, M
Abstract : Background: There are no recommendations regarding endovascular treatment (EVT) for patients with acute ischemic stroke (AIS) due to primary medium vessel occlusion (MeVO). The aim of this study was to examine the willingness to perform EVT among stroke physicians in patients with mild, yet personally-disabling deficits due to MeVO. Methods: In an international survey consisting of 4 cases of primary MeVOs, participants were asked whether the presence of personally-disabling deficits would influence their decision-making for EVT despite the patients having low NIHSS scores. Decision rates were calculated based on physician characteristics. Clustered univariable logistic regression was performed. Results: 366 participants from 44 countries provided 2562 answers. 56.9% opted to perform EVT in scenarios in which the deficit was relevant to the patient's profession versus 41.0% in which no information regarding patient profession was provided (RR1.39, p<0.001). The largest effect sizes were seen for female participants (RR1.68, 95%CI:1.35-2.09), participants >60 years (RR1.61, 95%CI:1.23-2.10), with more neurointervention experience (RR1.60, 95%CI:1.24-2.06), and who personally performed >100 EVTs per year (RR1.63, 95%CI:1.22-2.17). Conclusions: The presence of a patient-relevant deficit in low NIHSS AIS due to MeVO is an important factor for EVT decision-making. This may have relevance for the conduct and interpretation of low NIHSS EVT randomized trials.